ANTIMICROBIAL ACTIVITY OF THREE MEDICINAL PLANTS - Sirag, Nizar; Yassin, Sitelbanat; Yousif, Mirghani A (مجلة الجزيرة للعلوم الصحية; مجلد 5 عدد 2 (2009), 2009)
Background: Medicinal plants have been traditionally used for different kinds of ailments including infectious diseases. Objectives: The present work was undertaken to investigate the antimicrobial activity of three plants used in folk medicine. Methods: Plant extracts of ( Quercus infectoria , Glycyrrhiza glabra and Lepidium virginicum ) were in vitro tested against four bacterial strains and one type of fungi for their antimicrobial activitie s by using well diffusion techniques. Results: The ethanolic extracts of these plants showed varying results. Quercus infectoria was found to possess the highly marked antibacterial activity against both E. coli and Staphylococcus aureus while Glycyrrhiza glabra exhibited a significant antibacterial effect against Pseudomonas aurginosa . Lepidium virginicum produced antibacterial activity against E.coli . Both Quercus infectoria and Lepidium virginicum caused a considerable antifungal effect, while Glycyrrhiza glabra devoid of such antifungal activity. Conclusion: The three tested plant extracts could be considered as potential sources of new antimicrobial agents. Further researches should be made to isolate compounds responsible for antimicrobial activities.